Design of an appliance switch responding to solar energy - Koshti, Ambalika Pradip; Williams, Arthur (European Association for the Development of Renewable Energies, Environment and Power Quality, 2017)
Knowing the ill effects of dependence upon conventional resources for generation of energy, the world is already making an effort to harness energy from renewable energy sources. However, the use of conventional resources is not fully eliminated from daily lives of people as the renewable energy sources are limited due to their intermittent nature. The paper presents a unique technique of Demand Side Management (DSM) for a domestic consumer whose house is equipped with on-grid solar PV panel system. DSM is the management of energy needs according to its availability. The paper deals with designing of an automated switch which is an adapter and can be inserted into standard 13amp socket. The adapter is equipped with a sensor that transmits data to it. The smart solar switch can detect surplus power generated by the PV system and it controls non-priority loads in the house depending upon the amount of surplus power. The designed switch provides an automatic, fast, easy to install and safe option for customers who want to increase their use of solar energy. Its performance was tested in a lab setup as well as in real time scenario in a home.